2017
DOI: 10.1089/acm.2016.0417
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness-Based Relapse Prevention for Methadone Maintenance: A Feasibility Trial

Abstract: Results from this initial pilot trial support feasibility and acceptability, and provide preliminary data on outcomes for future trials of mindfulness-based approaches within the MMT community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 14 publications
0
14
0
1
Order By: Relevance
“…Given the intersection of pain with OUD and AUD, behavioral interventions that have been shown to be effective for OUD, AUD, and chronic pain are particularly appealing. For example, mindfulness-based interventions have been shown to be effective in the treatment of polysubstance use (Bowen et al, 2014; Witkiewitz et al, 2014b), opioid treated chronic pain (Garland et al, 2017), chronic pain (Veehof et al, 2016), and can be feasibly combined with methadone maintenance treatment (Bowen et al, 2017). Cognitive behavioral treatment (CBT) has long been supported as efficacious in the treatment of alcohol and SUDs (Magill and Ray, 2009) and while CBT has mixed evidence for chronic pain (Williams et al, 2012) and OUD (Fiellin et al, 2013; Moore et al, 2016), there may be advantages to offering integrated CBT treatment for pain and AUD/OUD.…”
Section: Treatment Of Comorbid Oud and Audmentioning
confidence: 99%
“…Given the intersection of pain with OUD and AUD, behavioral interventions that have been shown to be effective for OUD, AUD, and chronic pain are particularly appealing. For example, mindfulness-based interventions have been shown to be effective in the treatment of polysubstance use (Bowen et al, 2014; Witkiewitz et al, 2014b), opioid treated chronic pain (Garland et al, 2017), chronic pain (Veehof et al, 2016), and can be feasibly combined with methadone maintenance treatment (Bowen et al, 2017). Cognitive behavioral treatment (CBT) has long been supported as efficacious in the treatment of alcohol and SUDs (Magill and Ray, 2009) and while CBT has mixed evidence for chronic pain (Williams et al, 2012) and OUD (Fiellin et al, 2013; Moore et al, 2016), there may be advantages to offering integrated CBT treatment for pain and AUD/OUD.…”
Section: Treatment Of Comorbid Oud and Audmentioning
confidence: 99%
“…Indeed, one study demonstrated the feasibility and acceptability of a 6-week mindfulness-based program for methadone patients. 42 Future researchers should examine the impact of these, and other, adjunct interventions on treatment adherence and outcomes across different forms of medication-assisted treatment.…”
Section: Adjunctive Behavioral Interventions With Medication-assistedmentioning
confidence: 99%
“…There are limited evidence-based CAM treatments that have been adequate in controlling chronic pain, but not much on analgesic reduction [9] (Table 1). Bowen et al [25] Meditation Amatya et al [12] Pray, Religion, and Spirituality Drebenstedt [22] Biofeedback Chrousos et al [23] Guide Imaginary Day et al [24] Music Therapy Taylor et al [26] Traditional Medicine of China and India Acupressure Kumar et al [21] Eccleston et al [29] Acupuncture Wren et al [27] Wren et al [27] Ayurvedia Siddha Zhang et al [28] Summarizes most of CAM modalities used for chronic pain management and analgesic misuse prevention. Our study provides an evaluation of the effectiveness and limitations of CAM treatments in the prevention and treatment of chronic pain and analgesic reduction.…”
Section: Introductionmentioning
confidence: 99%